HAM AND ISLAMIC LAW: DEATH PENALTY ON THE CRIME OF NARCOTICS ABUSE - Mirsa Astuti (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to examine the death penalty in the crime of narcotics abuse according to the views of human rights and Islamic law.The research method is descriptive analysis which leads to juridical normative research. Sources of data used are primary secondary legal matrials, namely the Koran and laws and secondary lawa namely in the form of book, scientific journals. The results of the study show that the death penalty for convicted persons in the criminal case of narcotics abuse in the view of human rights refers to article 1 paragraph 2 of Law No.39 of 1999 concerning Human Rights that narcotics convicts cannot fulfill their obligations as stated in article 1 paragraph 1 the law, namely violating the right to life of the general public which is protected by law.So that convicted narcotics can be sentenced to death because they are deemed not entitled to their human rights, namely the right to life. In Islamic law, convicted of narcotics abuse crime can be categorized as having committed destruction and injustice in this world.Keywords: Death Penalty, Narcotics, Human Rights, Islamic Law